2022
DOI: 10.1021/acs.jmedchem.1c02148
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the Clinical Candidate MAK683: An EED-Directed, Allosteric, and Selective PRC2 Inhibitor for the Treatment of Advanced Malignancies

Abstract: Polycomb Repressive Complex 2 (PRC2) plays an important role in transcriptional regulation during animal development and in cell differentiation, and alteration of PRC2 activity has been associated with cancer. On a molecular level, PRC2 catalyzes methylation of histone H3 lysine 27 (H3K27), resulting in mono-, di-, or trimethylated forms of H3K27, of which the trimethylated form H3K27me3 leads to transcriptional repression of polycomb target genes. Previously, we have shown that binding of the lowmolecular-we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 42 publications
(147 reference statements)
3
21
0
Order By: Relevance
“…Importantly, ZJH-16 exhibited excellent oral bioavailability ( F = 94.7%). In contrast, after oral dosing of EED226 at 2 mg/kg, the AUC, T 1/2 , and F were 1948 nM h, 1.6 h, and 62%, respectively . The results demonstrate that ZJH-16 has a better oral bioavailability than EED226.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Importantly, ZJH-16 exhibited excellent oral bioavailability ( F = 94.7%). In contrast, after oral dosing of EED226 at 2 mg/kg, the AUC, T 1/2 , and F were 1948 nM h, 1.6 h, and 62%, respectively . The results demonstrate that ZJH-16 has a better oral bioavailability than EED226.…”
Section: Resultsmentioning
confidence: 81%
“…In contrast, after oral dosing of EED226 at 2 mg/kg, the AUC, T 1/2 , and F were 1948 nM h, 1.6 h, and 62%, respectively. 36 The results demonstrate that ZJH-16 has a better oral bioavailability than EED226. Collectively, the PK studies suggest that ZJH-16 has acceptable PK profiles in male rats and is suitable for carrying out further in vivo antitumor studies.…”
Section: Zjh-16mentioning
confidence: 90%
See 1 more Smart Citation
“…Lastly, compounds containing triazolopyridine ring were evaluated for their bioactivities, such as anti-inflammatory, p38R, 11beta-hydroxysteroid dehydrogenase-type 1 (11beta-HSD-1), prolylhydroxylase domain-1 (PHD-1), myeloperoxidase, tubulin polymerization, polycomb repressive complex 2 (PRC2) inhibitory, HIV-1 allosteric inhibitor activity, mGlu receptor 2 (mGluR2) PAM, muscarinic acetylcholine receptor subtype 1 (M1) PAM, and retinoic acid receptor-related orphan nuclear receptor gama-t (RORγt) inverse agonist [174,[291][292][293][294][295][296][297][298][299][300][301][302][303].…”
Section: Triazolopyridinesmentioning
confidence: 99%
“…Furthermore, gene expression microarray and Chip-PCR experiments revealed that PRC2-regulated gene expression was significantly increased by treatment with EED226 and was similar to that of EZH2 catalytic inhibitor (EI1) treatment, demonstrating that EED226 also has a significant inhibitory effect on the gene-silencing function of PRC2 [ 278 ]. Interestingly, although EED226 failed to enter clinical trials, another EED inhibitor, MAK683, developed on the basis of this scaffold, is currently in phase 2 clinical trials for the treatment of lymphoma ( Table 3 ) [ 280 ]. Moreover, EEDi-5285 is the most potent EED inhibitor that has been reported, and it achieves complete and long-lasting tumor regression in mice, further suggesting great potential for the treatment of PRC2-dependent cancers by inhibiting the EED-H3K27me3 interaction [ 279 ].…”
Section: Polycomb Repressive Complexes In Cancermentioning
confidence: 99%